Respuesta :
Answer:
If you would like to write a * b + c in simplest form, you can do this using the following steps:a = x + 1b = x^2 + 2x - 1c = 2xa * b + c = (x + 1) * (x^2 + 2x - 1) + 2x = x^3 + 2x^2 - x + x^2 + 2x - 1 + 2x = x^3 + 3x^2 + 3x - 1The correct result would be x^3 + 3x^2 + 3x - 1.
Step-by-step explanation:
AB + C in simplest form is x³ + 3x² + 3x - 1.
What is a Polynomial?
- It is an algebraic expression containing constants and variables, where the variable have the exponents.
- It is important mathematical function used in most of the calculus.
Given: Variables A, B and C.
A = x + 1
B = x² + 2x - 1
C = 2x
⇒ AB + C = (x + 1)(x² + 2x - 1) + 2x
⇒ AB + C = x(x² + 2x - 1) +1(x² + 2x - 1) + 2x
⇒ AB + C = x³ + 2x² - x + x² + 2x - 1 + 2x
⇒ AB + C = x³ + 3x² + 3x - 1
Therefore, the simplest form of AB + C is x³ + 3x² + 3x - 1.
Learn more about the Polynomials here: https://brainly.com/question/16306595
#SPJ2